Forming a Solid Foundation: The Role of Early Childhood Education in Character Development - Ginting, Tarissa Gunaly (Walidem Institute and Publishing (WIP), 2024)
This article highlights the important role of education in the early stages of a child's development in shaping positive values, attitudes, and behaviours. Formation of a Solid Foundation: The Role of Early Childhood Education in Character Development is an in-depth topic on the significance of early childhood education in forming strong and ethical character through an interdisciplinary approach method, this article combines the concepts of developmental psychology, education, and ethics to explore how early childhood education can provide a solid foundation for good character development. Conduct a thorough literature review of research related to character formation in early childhood, theories of child development, and practices of character education at the preschool level. By emphasizing the importance of value-oriented parenting, positive social interaction, and appropriate intellectual stimulation, this article considers how early childhood education practices can help children become responsible, caring, and contributing individuals in society. Summarize the conclusions of the research and develop practical recommendations for early childhood education institutions in improving the effectiveness of character education practices. Thus, a better understanding of the role of early childhood education in character development can provide a strong foundation for empowered human development efforts in the future.